2010
DOI: 10.1016/j.ympev.2009.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and DNA barcoding of inquiline oak gallwasps (Hymenoptera: Cynipidae) of the Western Palaearctic

Abstract: The NERC and CEH trade marks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. We examine phylogenetic relationships within the Synergus complex of herbivorous 50 inquiline gallwasps associated with (Hymenoptera; Cynipidae; Synergini) associated with cynipid host galls on oak, a biologically diverse group whose genus-level morphological taxonomy has long been considered stable but whose spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 74 publications
(109 reference statements)
5
54
2
Order By: Relevance
“…Probably all seven genera form together a distinct monophyletic lineage (Ronquist et al 2015) and Rhoophilus generally recovered as the sister taxon of all others (e.g. Ács et al 2010Ács et al , Ronquist et al 2015. The morphological taxonomy of Synergus complex has been studied in details (Mayr 1872;Wiebes-Rijks, 1979;Nieves-Aldrey & Pujade-Villar 1985PujadeVillar & Nieves-Aldrey 1990Liljeblad & Ronquist 1998;Liljebald et al 2008;PujadeVillar et al 2003, Melika 2006Bozsó et al 2015) and (i) supported the differentiation of these two lineages, and (ii) showed that five genera, Agastoroxenia, Saphonecrus, Synergus, Synophrus and Ufo morphologically differs from Ceroptres .…”
Section: Prosopis) and Rhoophilus (Inquilines On Rhus Galls) Spread Lmentioning
confidence: 99%
See 4 more Smart Citations
“…Probably all seven genera form together a distinct monophyletic lineage (Ronquist et al 2015) and Rhoophilus generally recovered as the sister taxon of all others (e.g. Ács et al 2010Ács et al , Ronquist et al 2015. The morphological taxonomy of Synergus complex has been studied in details (Mayr 1872;Wiebes-Rijks, 1979;Nieves-Aldrey & Pujade-Villar 1985PujadeVillar & Nieves-Aldrey 1990Liljeblad & Ronquist 1998;Liljebald et al 2008;PujadeVillar et al 2003, Melika 2006Bozsó et al 2015) and (i) supported the differentiation of these two lineages, and (ii) showed that five genera, Agastoroxenia, Saphonecrus, Synergus, Synophrus and Ufo morphologically differs from Ceroptres .…”
Section: Prosopis) and Rhoophilus (Inquilines On Rhus Galls) Spread Lmentioning
confidence: 99%
“…For example the presence of cryptic species, independently evolving lineages that are morphologically indistinguishable, had been demonstrated in many times (Ács et al 2010(Ács et al , Kaartinen et al 2010. Consequently it is becoming increasingly common to supplement morphological identifcation with molecular methods such as DNA barcoding (Hebert et al 2003).…”
Section: Prosopis) and Rhoophilus (Inquilines On Rhus Galls) Spread Lmentioning
confidence: 99%
See 3 more Smart Citations